Penerapan Aplikasi WPS Office Sebagai Pembelajaran Alternatif Bagi Siswa SMK Muhammadiyah 3 Pekanbaru - Boy Zidan Nadjal; Qonaah Nuryan Arif (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
Muhammadiyah Vocational High School (SMK) 3 Pekanbaru city is an educational institution under the Muhammadiyah Business Charity (AUM) which equips its students with vocational training and Al-Islam Kemuhammadiyahan values. The problems faced are 1) Services to students are not yet supported by adequate facilities 2) Schools have limited internet access for students. Of the several problems that exist at the school, service is prioritized on the problem of limited computer facilities. The solution offered to schools to overcome some of these problems is to use the WPS office application as a learning alternative. This shows that WPS Office is effectively used as alternative learning for students at SMK Muhammadiyah 3 Pekanbaru